Long-Term Outcomes of Patients Undergoing Percutaneous Coronary Intervention (PCI) for Chronic Total Occlusions - Bahauddin Khan, Amir Taj Khan, Afnan Muhammad, Shah Sawar, Fouzia Rahman, Mahmood Ul Hassan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Percutaneous coronary intervention (PCI) is a minimally invasive procedure used to treat patients with coronary artery disease. Chronic total occlusions (CTO) occur when a coronary artery is completely blocked for more than 3 months. Objectives: The main objective of the study is to find the long-term outcomes of patients undergoing percutaneous coronary intervention (PCI) for chronic total occlusions. Material and methods: The retrospective cohort study was conducted at the Hayatabad Medical Complex in Peshawar, Pakistan from June 2019 to June 2020. The study included 384 patients who underwent PCI for chronic total occlusions. Data were collected from patient records and follow-up visits. The primary outcome of the study was all-cause mortality, while the secondary outcomes included major adverse cardiovascular events (MACE), repeat revascularization, and quality of life. Data were analyzed using descriptive statistics and survival analysis. Result: The results of the retrospective cohort study investigating the long-term outcomes of patients who underwent PCI for chronic total occlusions showed that the study included 384 patients who underwent PCI for at least one chronic total occlusion. The mean age of the patients was 60.3 years, and 76.3% were male. Conclusion: In conclusion, this study suggests that percutaneous coronary intervention (PCI) for chronic total occlusions (CTOs) can provide good long-term outcomes with an overall success rate of 87.5%.